Specificity of French Bean (Phaseolus vulgaris L.) Genotypes and Rhizobium phaseoli Strains to Establish Symbiotic N-fixation in Inceptisols of Varanasi, Uttar Pradesh, India - Yadav, Janardan (International Journal of Bio-resource and Stress Management, 2023)
A pot experiment consisted of 15 treatment combinations of 5 genotypes of Phaseolus vulgaris L. (G1=HUR 15, G2= IC 14919, G3=DARL 1136, G4=DARL 1434 and G5=PI 175822) and 2 strains of Rhizobium leguminosarum biovar phaseoli along with a control (I0=Control, I1=USDA 2667 and I2=USDA 2676) was carried out in triplicates under factorial randomized block design (FCRBD) during rabi season of 2006-07 at Banaras Hindu University, Varanasi (Uttar Pradesh). Among the genotypes, G2 (IC 14919) revealed superiority in nodulation and plant growth at flowering stage with higher grain yield (3.06 g plant-1), N content (3.50%) and its uptake (0.016 mg plant -1) at par values with G5. The Rhizobium strain USDA 2676 was comparatively superior for higher nodulation and nitrogen fixation with each of the genotypes. However, the most effective Rhizobium strain Phaseolus vulgaris genotypes specificity was seen in between USDA 2676 and G2 with maximum grain yield (3.56 g plant-1), N content in grain (3.67%) and its uptake /grain (0.018 mg plant-1) followed by strain USDA 2676 and G5 . The results indicate that the success of symbiotic N- fixation in French bean (common bean) is highly dependent on strain-genotypes specificity and thus, it should be further tested in field conditions to popularize its cultivation at low fertilizer N input in eastern part of Uttar Pradesh, India.